Construction of Generation Z's Monotheism on Social Media: A Phenomenological Study of UIN Palu Students - Nursyam Nursyam; Kamridah Kamridah; Rusli Takunas; Naimah; Makmur Harun (Nadwa: Jurnal Pendidikan Islam, 2025)
Digital transformation fundamentally altered how Generation Z constructs aqidah (theology), making social media the primary religious information source and challenging traditional authorities. This study is vital because theological fragmentation risks superficiality and cognitive dissonance among future religious educators. Prior research neglected the specific phenomenological process of tauhid (monotheism) construction by Gen Z. Utilizing Husserl’s transcendental phenomenology, this qualitative study explored the "lived experience" of 18 Islamic Religious Education (PAI) students at UIN Datokarama Palu. Active social media users, selected via purposive sampling, were analyzed using Moustakas's method following in-depth interviews and digital document analysis. The key finding is "Digital Epistemological Bricolage," characterized by five themes: liquid faith, algorithmic authority, micro-content theology, emotional resonance, and dialogical construction. The study concludes that religious authority has shifted from scholarly capacity to digital metrics. This urgently requires transformative pedagogy in Islamic higher education that integrates critical digital religious literacy to preserve theological depth.